Isolation, characterization and efficacy of lytic bacteriophages against pathogenic Escherichia coli from hospital liquid waste - Rahmad Lingga; Sri Budiarti; Iman Rusmana; Aris Tri Wahyudi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Lingga R, Budiarti S, Rusmana I, Wahyu AT. 2020. Isolation, characterization and efficacy of lytic bacteriophages against pathogenic Escherichia coli from hospital liquid waste. Biodiversitas 21: 3234-3241. Escherichia coli is known as a pathogenic contaminant bacteria in hospital wastewater hazardous to humans and the environment. Concerns about the emergence of chlorine- and antibiotic-resistant bacteria increase the urgency to find an alternative strategy to control pathogenic bacteria in hospital wastewater. One of the alternatives is using lytic bacteriophage. This study aimed to isolate, characterize, and examine the efficacy of lytic bacteriophage against pathogenic Escherichia coli from hospital wastewater. It isolated, characterized (plaque morphology, host range, virion electron micrograph, and sensitivity to temperature, pH, and chlorine treatments), and tested the efficacy of lytic bacteriophages in controlling pathogenic E. coli isolated from hospital wastewater. Five phages were successfully obtained, all of which had clear plaques (lytic phage character). Based on host range assay, most of the phages could lyse all tested E. coli strains but not for other species. Electron micrograph photography revealed that the phages belonged to Myoviridae. The phages showed stability in high temperature, broad-ranged pH, and high concentrations of chlorine treatments. Assay on phages efficacy suggested that the phages are capable of significantly reducing the E. coli population both in sterilized and non-sterilized wastewater. The combination of phage treatment and chlorine was more effective than single phage treatment. The efficacy test revealed that phage application in wastewater had the best result seen from cocktail treatment and a combination of phage treatment and chlorine. These results suggested that the phage can be a potential candidate for disinfection purposes.